H2O2 alleviates salt stress effects on photochemical efficiency and photosynthetic pigments of cotton genotypes - Luana L. de S. A. Veloso; Carlos A. V. de Azevedo; Reginaldo G. Nobre; Geovani S. de Lima; Jessica D. Capitulino; Francisco de A. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the quantum yield and concentrations of photosynthetic pigments of naturally colored cotton genotypes under irrigation with waters of different electrical conductivities and foliar applications of hydrogen peroxide. The design used was randomized blocks in a 4 × 3 × 2 factorial arrangement, corresponding to four concentrations of hydrogen peroxide - H2O2 (0, 25, 50 and 75 μM), three genotypes of colored fiber cotton (‘BRS Rubi’, ‘BRS Topázio’ and ‘BRS Verde’) and two values of electrical conductivity of water (0.8 and 5.3 dS m-1), with three replicates. Irrigation with water of 5.3 dS m-1 reduces the chlorophyll a, chlorophyll b and total chlorophyll concentrations of ‘BRS Rubi’ cotton. The concentrations of photosynthetic pigments, maximum fluorescence, variable fluorescence and quantum efficiency of photosystem II of ‘BRS Rubi’ cotton increased under irrigation with 0.8 dS m-1 water and foliar application of 50 μM of hydrogen peroxide. Water of 5.3 dS m-1 and foliar applications of 75 μM of hydrogen peroxide reduce the concentrations of photosynthetic pigments, but did not cause damage to the efficiency of photosystem II of the colored cotton genotypes.